Genetic Diversity of MSP1 Block 2 of Plasmodium vivax Isolates from Manaus (Central Brazilian Amazon) - Leidiane Amorim Soares; Janaína Evangelista; Patricia Puccinelli Orlandi; Maria Edilene Almeida; Luciana Pereira de Sousa; Yury Chaves; Roberto Barbosa-Filho; Marcus Vinícius Lacerda; Luis André Mariuba; Paulo Afonso Nogueira (Journal of Immunology Research)
The diversity of MSP1 in both Plasmodium falciparum and P. vivax is presumed be associated to parasite immune evasion. In this study, we assessed genetic diversity of the most variable domain of vaccine candidate N-terminal PvMSP1 (Block 2) in field isolates of Manaus. Forty-seven blood samples the polymorphism of PvMSP1 Block 2 generates four fragment sizes. In twenty-eight of them, sequencing indicated seven haplotypes of PvMSP1 Block 2 circulating among field isolates. Evidence of striking exchanges was observed with two stretches flanking the repeat region and two predicted recombination sites were described. Single nucleotide polymorphisms determined with concurrent infections per patient indicated that nonsynonymous substitutions occurred preferentially in the repeat-rich regions which also were predicted as B-cell epitopes. The comprehensive understanding of the genetic diversity of the promising Block 2 associated with clinical immunity and a reduced risk of infection by Plasmodium vivax would be important for the rationale of malaria vaccine designs.